Erratum: Fiber-tip endoscope for optical and microwave control (Review of Scientific Instruments (2022) 93 (095104) DOI: 10.1063/5.0100330) - Dix, Stefan; Gutsche, Jonas; Waller, Erik; Von Freymann, Georg; Widera, Artur (Review of Scientific Instruments, 2022)
This article was originally published online on 29 September 2022 with an error in the affiliation. The affiliation appears correct above. All online versions of this article were corrected on 3 October 2022; the article is correct as it appears in the printed version of the journal. AIP Publishing apologies for this error.
CRIS-Team Scopus Importer:2023-03-27